The man who hated work and loved labor : the life and times of Tony Mazzocchi - Leopold, Les (Vermont, 2007)
"Leopold (cofounder & director, Labor Inst. & Public Health Inst.) tells the story of radical unionist Tony Mazzocchi (1926-2002), who grew up in left-wing New York. In 1953, Mazzocchi, a World War II veteran, followed his employer, Helena Rubinstein, from New York City to Long Island and rebuilt his union, Local 149, United Gas, Coke and Chemical Workers, which became the Oil, Chemical and Atomic Workers (OCAW) International Union in 1955. The author shows how Mazzocchi thus strengthened America's labor movement, not to mention the local Democratic Party, mixing radical politics with union fights for better wages and better work conditions. The result: a militant and popular union local. Mazzocchi used his national position at OCAW to work with scientists and environmentalists to improve workplace safety, environmental laws, and economic equality. His radicalism angered conventional unionists, especially those assisting the CIA abroad. He irritated corporations, and was considered a threat to and by the FBI. Leopold's admiring biography shows Mazzocchi as that rare radical who escaped the Red Scare and continued through old age to weave together leftist politics and strong unionism with the goal of improving life for all Americans. "